Design of triangular core LMA-PCF with low-bending loss and low non-linearity for laser application. (July 2016) - Kabir, Sumaiya; Khandokar, Md. Rezwanul Haque; Khan, Muhammad Abdul Goffar
Abstract: In this paper we characterize the design of a simple large-mode area photonic crystal fiber (LMA-PCF) with low bending loss and low non-linearity. The finite element method (FEM) with perfectly matched boundary layer (PML) is used to investigate the guiding properties. According to simulation the characterized four ring fluorine doped triangular core LMA-PCF achieves 1500 µm 2 effective mode area with a low bending loss of 10 -5 dB/km at the wavelength of 1.064 µm and at a bending radius of 40 cm which is suitable for high power fiber laser. Highlights: Simple large-mode area photonic crystal fiber using fluorine-doped silica as 1st ring. Effective area 1500 µm 2 with a low bending loss of 10 −5  dB/km at a bending radius of 40 cm. The non-linear coefficient of the design is also low. A potential candidate for high power fiber laser.